Zakat for Disabilities: Bridging Indonesian State Law and Islamic Law - Chandra, Muhammad Fiqih Rizqi; Muhammad Rizky Siddiq (Invest Journal of Sharia & Economic Law, 2024)
This study aims to disclose the impact of Islamic law and Indonesian state law on organizing zakat distribution for persons with disabilities. Utilizing a descriptive comparative methodology, this study analyzes how both Islamic law and Indonesian state law influence efforts to provide zakat funds to people with disabilities in Indonesia. We examined scholarly literature, reports, articles on Fiqh Zakat, zakat distribution, the rights of people with disabilities, and regulations to obtain pertinent background knowledge. A comparative analysis assessed the impact of the similarities and differences between these laws on the right to receive zakat. The findings evaluate the contribution of zakat distribution to addressing the needs of people with disabilities from the perspectives of both Islamic law and state law. This study emphasizes the importance of protecting individuals with disabilities in various countries, including those with secular legal frameworks, as a crucial aspect of social policies. It advocates equal access to education, healthcare, and employment opportunities, fostering inclusivity and eliminating discrimination.